Effect of ascorbic acid on chemical content and viability of cocoa seed after storage. - Willy Arnold Daniel Sekewael; Endang Pudjihartati; Teguh Iman Santoso (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2019)
Storage of oily seeds will give the seeds deteriorated faster due to oil auto-oxidation. It will changes the biochemical and physiological of the seeds. Reducing sugar, protein and fat are biochemical compound those support the seeds during germination. Auto-oxidation of fat can produce free fatty acids whichcause seeds to lose viability and vigor during storage. Application of antioxidant can prevent the activity of auto-oxidation. This research aimed to study the effect of ascorbic acid to minimize the deterioration by observing the chemical content and viability of Theobroma cacao L. seeds. It was conducted at KaliwiningExperimental Station, Indonesian Coffee and Cocoa Research Institute, Jember, East Java and at Satya Wacana Christian University, Salatiga, Central Java. The research used completely randomized design and T-test analysis. The treatments consisted of four ascorbic acid concentrations, i.e. 0 ppm as control, 250 ppm, 300 ppm, and 350 ppm. The treated cacao seeds were stored for two shelf life i.e. 1 week and 2 weeks. Each treatment was repeated with seven replications. Data analysis used SAS 9.0. The results showed that application 250 and 300 ppm of ascorbic acid increased reducing sugar, protein content decreased fat and free fatty acid content of cocoa seeds. Application of 350 ppm of ascorbic acid decreased reducing sugar, protein, fat content and increased free fatty acid content of cocoa seeds. Application of ascorbic acid with concentration of 250 ppm and 300 ppm could maintain cocoa seeds viability upto 2 weeks of shelf life.